The Recovery Room: Transition from a Sleepy Postoperative Unit to a Vibrant and Cost-Effective Multipurpose Perioperative Care Unit - Schad S; Booke H; Thal SC; Bentley AH; Booke M (Dove Medical Press, 2021)
Stefan Schad,1 Hendrik Booke,2 Serge C Thal,3 Alexander H Bentley,3 Michael Booke1 1Department of Anesthesiology, Intensive Care Medicine and Pain Therapy, Kliniken-MTK, Academic Hospital of the Goethe-University Frankfurt, Frankfurt, Germany; 2Department of Anesthesiology, Intensive Care Medicine and Pain Therapy, University Hospital Frankfurt, Goethe University, Frankfurt, Germany; 3Department of Anesthesiology, HELIOS University Hospital Wuppertal, Witten/Herdecke University, Wuppertal, GermanyCorrespondence: Stefan Schad Email sschad@kliniken-mtk.deAbstract: The anesthesiologist, who traditionally was solely responsible for the intra- and postoperative care of patients, has undergone a transformation over the last decades and has emerged as a specialist for perioperative medicine. This includes preoperative assessment, preoperative stabilization of emergent cases, pre- or postoperative initiation of regional blocks, postoperative recovery and if needed postoperative intensive care outside the intensive care unit. A traditional recovery room, designated to take care of patients emerging from anesthesia only, no longer matches the modern anesthesiologist's demands. However, a traditional recovery room can easily be transformed into a vibrant multi-purpose perioperative care unit. Especially in smaller hospitals, this serves to match the anesthesiologist's demands without the financial burden of separate units for each task. On the contrary, it allows to transform the recovery room from a mandatory, but costly postoperative unit into a highly productive and demanding perioperative unit, allowing for extra revenues without corresponding costs. Worldwide, operating rooms are linked to an adjacent recovery room allowing patients to emerge from anesthesia until they fulfill the criteria to be transferred either to the regular ward or, in case of outpatient surgery, to be discharged home. Running these recovery rooms, however, is expensive due to the required technical equipment and the monthly costs of highly qualified anesthesia personnel. Despite these financial burdens, such recovery rooms are still mandatory to ensure full recovery after anesthesia and surgery. In most countries, there is no (full) reimbursement for providing recovery rooms, turning them into fiscally deficient units in most hospitals. However, recovery rooms can be further developed allowing hospitals to improve their caseloads, reduce turnover times in the operating room, and even help to manage a shortage of beds in the intensive care unit. In this paper, we describe the potential transformation from a traditional recovery room to a multi-purpose perioperative high-tech unit.Keywords: recovery room, postanesthesia care unit, perioperative medicine, turnover time, reimbursement, same-day admission, holding area